Developing environmentally sustainable apparel through participatory design - Monfort-Nelson, Erin M. (Kansas State University, 2014)
Many sustainable garments do not engage wide consumer interest, nor encourage eco-conscious purchasing. Meanwhile, mass consumption of unsustainable apparel contributes to environmental degradation (Black, 2008). However, Niinimäki (2010) suggests that engaging consumers in the design and development of environmentally sustainable products could improve the balance between environmental design decisions and functional, aesthetic, and emotional qualities (Lamb & Kallal, 1992). The purpose of this practice-based research was to (a) identify apparel and environmental attitudes and consumption behaviors of potential sustainable apparel consumers, (b) generate sustainable apparel design concept and product through use of participatory design methods, and (c) evaluate the sustainable concept, product, and participatory method. The sample was 10 female university students. Consumer data was collected through an online (i.e., Facebook) ethnographic journal and a focus group. Qualitative analysis generated the target market’s ideal apparel characteristics and ideal environmental apparel characteristics as apparel offering versatility and variety within their existing wardrobes; elements expressive of their personalities; simple and inexpensive maintenance; organic or recycled materials; and less textile waste at disposal. Additionally, it was determined that participants had low knowledge of the apparel and textile industry and its environmental impacts. Generation of sustainable apparel design ideas occurred through a second focus group session. Analysis of the focus group data, combined with the researcher’s tacit sustainable design knowledge, formed a design concept. The sustainable apparel design concept was comprised of three characteristics reflective of the target market’s ideals and design suggestions: be versatile through various temperatures; social settings, and environments; be convertible through temporary adjustment of functional and aesthetic elements; and be transitional allowing the garment to be layered for greater thermal insulation without detracting from the appearance. The sustainable apparel concept was an application of the pre-existing Design for User Interaction sustainable design strategy. The sustainable apparel design concept was then applied to the development of an outerwear garment and presented to the participants and mentors as a digital sketch. The design addressed the sustainable design concept through interchangeable envelope-style shell layers, an insertable thermal core layer, a buttoned closure at the hemline and interconnecting button points for added alignment between layers. In this garment, the researcher applied participants’ suggestions of style, materials, and inclusion of a core layer. Following sketch refinement, two prototypes were constructed. The first prototype consisted of a thermal core layer and outer coat layer. Due to challenges with the core layer fabric, the second prototype modified the core layer material and style. Additionally, in the second prototype, the shell was made sleeveless and both a bolero style jacket and lining were added. Dual button fasteners connected the layers. During the third focus group session, participants evaluated the design concept, second garment prototype, and the participatory design methods. Participants noted that the design concept provided increased ease of garment care (which could potentially increase the frequency of laundering); ease of garment storage; and increased versatility through varying temperatures. Participants’ suggestions for prototype refinement included the addition of a kick-pleat and reduction of button alignment points. Prototype development did not reach completion during this study. Further refinement of the garment’s pattern and fit, implementation of additional aesthetic/functional elements, and development of an intuitive transformation are necessary. Participant evaluation of participatory methods and study participation were the use of Facebook as an online ethnographic journal made daily participation easy and allowed the researcher to become familiar with their personalities, increasing their comfort at later stages of the research. Participants felt their suggestions were evident in the garment prototype and were as involved as their experience and knowledge allowed. The only participant suggestion regarding the participatory design experience was the addition of updates informing participants of the design progress between focus group sessions. Though the concept and resulting garment were not exceedingly original, participants were pleased with the fruition of their ideas. This finding indicates a willingness to participate in the design process, supportive of participatory design.
Keywords: Apparel design; Practice-based research; Sustainability; Participatory design; Millennial consumers; Design process; Design (0389); Social Research (0344); Sustainability (0640)